The pigeonpea genome - Varshney, R. K. 1973-; Saxena, Rachit K.; Jackson, Scott A. (Springer, 2017)
Pigeonpea (Cajanus cajan) is a crop of small land holding farmers in arid and semi-arid regions of the world. It has a number of usages starting from protein rich food to vegetarian families; fuel wood; nitrogen supplier to soil; recycling minerals in soil to animal feed etc. Pigeonpea has been considered to be originated and domesticated in central India from where it travelled to different parts of the world such as Africa and Latin America. In ongoing scenario of climate change, biotic and especially abiotic stresses will make the conditions more challenging for entire agriculture. This volume focusing on the pigeonpea genome will collate the information on the genome sequencing and its utilization in genomics activities, with a focus on the current findings, advanced tools and strategies deployed in pigeonpea genome sequencing and analysis, and how this information is leading to direct outcomes for plant breeders and subsequently to farmers.
Keywords: Pigeon pea -- Genetics.; elektronické knihy; electronic books